Ultrasound-guided peribulbar block in dromedary camels: a descriptive cadaveric study - Marzok, Mohamed; Almubarak, Adel; Elkhidr, Rasha Yassin; Elkawi, Mohamed Abd; El-Sherif, Mohamed W. (BMC veterinary research, 2025)
Sternal recumbent procedures in camels using a balanced combination of sedatives and analgesics are gaining increasing clinical importance. Ultrasound-guided peribulbar nerve block (UG-PB) has been previously described in dogs, horses, and humans for facial and ocular surgeries, offering a lower risk of complications than the ultrasound-guided retrobulbar nerve block (UG-RB). However, its application to dromedary camels remains unexplored. To describe and evaluate a novel supraorbital UG-PB technique in camel cadavers and compare its injection site accuracy with that of transpalpebral UG-RB using computed tomography (CT) imaging. Twelve fresh cadaveric camel heads were used. The supraorbital UG‒PB technique was performed in the right orbit, whereas the UG-RB technique was applied in the left orbit of each cadaver head. The placement and spread of the contrast medium were confirmed via CT imaging. Statistical analysis was conducted to compare the success rates of each technique in achieving an accurate injection site placement. Compared with UG-RB (9/12), the UG-PB technique achieved 100% accuracy (12/12) for contrast medium placement. Three UG-RB injections resulted in extraconal contrast placement. Operator assessment indicated enhanced feasibility and clarity of anatomical visualization using the UG-PB approach. Compared with UG-RB, the UG-PB technique demonstrated superior accuracy in injection site placement. Its feasibility, precision, and potential safety advantages suggest its clinical applicability in ophthalmic procedures in camels. Further clinical studies are required to validate the efficacy, safety, and outcomes of this technique.